Analysis of Abdominal Respiratory Sensor Performance in Sleep Apnea Conditions - Dimas Adi tya; Endro Yulianto; Sumber Sumber (Jurnal Teknokes, 2023)
Abdominal respiratory sensor is a sensor used to detect sleep apnea that is specifically for neonates, this sensor is specifically for neonates because the use of this sensor does not require a voltage input to activate the sensor. In the absence of voltage input so as not to disturb the heart rhythm in neonates. When the sensor is no longer elastic, the pressure difference generated by the sensor will be unstable so that the sensor cannot work optimally. With these conditions, the period of use of the sensor needs to be known how durable the sensor is when it is used on patients so that the sensor can maximally detect the occurrence of apnea in neonates. How many times have you been in apnea. This study uses an Arduino microcontroller to process the pressure value and RR value generated by the stomach sensor and the MPX5010dp pressure sensor. the research method used is to use a simulator to analyze the combination of abdominal sensors and pressure sensors to monitor apnea. If viewed based on the average error, the error value in the RR 10bpm setting is ±0.185%, the RR 15 setting is ±0.245%, and the setting RR 20bpm is ±0.383%. From the average error value, it can be said that the higher the RR setting value, the higher the average error for each decrease in pressure output. it can be concluded that the performance of the use of the Abdominal Respiratory Sensor and Pressure Sensor on the Apnea Monitoring module functions well in detecting RR according to the settings on the simulator for 3-day monitoring. The development that can be done in this research is to use a more sensitive pressure sensor so that the results obtained are more stable and make the module display more attractive.